Enhancing food safety : the role of the Food and Drug Administration - Institute of Medicine (U.S.). Committee on the Review of Food and Drug Administration's Role in Ensuring Safe Food.; Wallace, Robert B., 1942-; Oria, Maria (Washington, D.C. : National Academies Press, 2010)
"Recent outbreaks of illnesses traced to contaminated sprouts and lettuce illustrate the holes that exist in the system for monitoring problems and preventing foodborne diseases. Although it is not solely responsible for ensuring the safety of the nation's food supply, the U.S. Food and Drug Administration (FDA) oversees monitoring and intervention for 80 percent of the food supply. The U.S. Food and Drug Administration's abilities to discover potential threats to food safety and prevent outbreaks of foodborne illness are hampered by impediments to efficient use of its limited resources and a piecemeal approach to gathering and using information on risks. Enhancing Food Safety: The Role of the Food and Drug Administration, a new book from the Institute of Medicine and the National Research Council, responds to a congressional request for recommendations on how to close gaps in FDA's food safety systems. Enhancing Food Safety begins with a brief review of the Food Protection Plan (FPP), FDA's food safety philosophy developed in 2007. The lack of sufficient detail and specific strategies in the FPP renders it ineffectual. The book stresses the need for FPP to evolve and be supported by the type of strategic planning described in these pages. It also explores the development and implementation of a stronger, more effective food safety system built on a risk-based approach to food safety management. Conclusions and recommendations include adopting a risk-based decision-making approach to food safety; creating a data surveillance and research infrastructure; integrating federal, state, and local government food safety programs; enhancing efficiency of inspections; and more. Although food safety is the responsibility of everyone, from producers to consumers, the FDA and other regulatory agencies have an essential role. In many instances, the FDA must carry out this responsibility against a backdrop of multiple stakeholder interests, inadequate resources, and competing priorities. Of interest to the food production industry, consumer advocacy groups, health care professionals, and others, Enhancing Food Safety provides the FDA and Congress with a course of action that will enable the agency to become more efficient and effective in carrying out its food safety mission in a rapidly changing world."--Publisher's description.
The food safety system : context and current status -- Adopting a risk-based decision-making approach to food safety -- Sharing the responsibility for a risk-based system : models of governance and oversight -- Creating an integrated information infrastructure for a risk-based food safety system -- Creating a research infrastructure for a risk-based food safety system -- Integrating federal, state, and local government food safety programs -- Enhancing the efficiency of inspections -- Improving food safety and risk communication -- Modernizing legislation to enhance the U.S. food safety system -- Achieving the vision of an efficient risk-based food safety system.
Includes bibliographical references.
Keywords: United States. -- Food and Drug Administration; United States. -- Food and Drug Administration; Food -- Safety measures -- Government policy -- United States; Food -- Safety regulations -- United States; Food Supply -- United States; Food Contamination -- prevention & control -- United States; Health Policy -- United States; Resource Allocation -- United States; Risk Assessment -- United States; United States Government Agencies -- United States